Blue Light Exposure Improving Cognitive Function by Increasing Serum Orexin Level in Shift Working Nurse at Sanglah Central Hospital Denpasar - Laksmidewi, Anak Agung Ayu Putri; Lestari, Yuliantry Indah; Mahadewi, Ni Putu Ayu Putri; Adnyana, I. Made Oka; Nuartha, Anak Agung Bagus Ngurah (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Nurses are one of the many jobs that use the shift work system. Nurses work lovingly, requiring high attention when working. Sleep disorders are often experienced by nurses who work shifting outside of normal working hours. Long sleep disorders can cause cognitive function disorders. AIM: This study aims to determine the effectiveness of exposure to blue light in improving cognitive function and serum orexin levels compared to exposure to white light. METHODS: An experimental study with a pre-test-post-test control group design. Subjects were divided into treatment groups (exposure to blue light) and the control group (exposure to white light) equally. Both groups assessed cognitive function scores using the MoCA-INA and examined serum orexin levels before and after light exposure. RESULTS: The mean increase in the cognitive function score of the treatment group (5.00; p < 0.001) was greater than the control group (0.417; p = 0.054) and the mean increase in serum orexin levels in the treatment group (1068, 244; p < 0.001) was greater than the control group (336,706; p = 0.052), the increase in the treatment group was found to be statistically significant. CONCLUSION: Exposure to blue light before carrying out night shift can increase cognitive function scores 5 times greater and increase serum orexin levels higher than exposure to white light on nurses.